Soil structure interaction (SSI) influences the seismic response of a regular isolated building of 3, 6 and 10 stories in moderately rigid soil - Paredes, Briayan Rojas (2024)
In most structural analyzes, Soil-Structure Interaction (SSI) is excluded, and it has been shown that SSI affects it depending on the type of structure and soil properties. Therefore, in this article, the structural response of an isolated system was analyzed, including the flexibility of the soil in moderately rigid soil, varying the number of levels of the building. To determine the dynamic coefficients of soil stiffness, NISTgcr 12-917-21 was used. Then, when determining the soil and isolator coefficients, two models are conducted for each structure: structure with isolator and structure with SSI + isolator. This study aimed to analyze the variations of the structural response of the 2 models, thus determining the feasibility of the SSI + LRB isolator in this type of soil. Likewise, it was determined to what extent the height of the building influences the period, the base displacements, the basal shear, and the maximum drift. Finally, it is concluded that for short-term regular buildings and on moderately rigid soil, the SSI does not affect or reduce the effectiveness of the LRB isolators. In addition, the isolated base structure experienced greater seismic effects compared to the isolated base + SSI structures.